2016
DOI: 10.1097/md.0000000000004802
|View full text |Cite
|
Sign up to set email alerts
|

Patient, hospital, and local health system characteristics associated with the use of observation stays in veterans health administration hospitals, 2005 to 2012

Abstract: Recent studies have documented that a significant increase in the use of observation stays along with extensive variation in patterns of use across hospitals.The objective of this longitudinal observational study was to examine the extent to which patient, hospital, and local health system characteristics explain variation in observation stay rates across Veterans Health Administration (VHA) hospitals.Our data came from years 2005 to 2012 of the nationwide VHA Medical SAS inpatient and enrollment files, Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Using the periprocedure trigger to measure AEs represents a more consistent and reliable, retrospective method for detecting and measuring AEs and harms during the critical phase of a procedure. Previous triggers that were intended to capture AEs because of patients being admitted to the hospital on the same day of their procedure has not been as effective within the VA, 17 most likely due to the high same-day admission rate in the VA for reasons other than postprocedure care (i.e., social reasons) 58 . In other words, as a result of the VA’s unique same-day admission rate (observation status), the same-day admission triggers are not as effective.…”
Section: Discussionmentioning
confidence: 99%
“…Using the periprocedure trigger to measure AEs represents a more consistent and reliable, retrospective method for detecting and measuring AEs and harms during the critical phase of a procedure. Previous triggers that were intended to capture AEs because of patients being admitted to the hospital on the same day of their procedure has not been as effective within the VA, 17 most likely due to the high same-day admission rate in the VA for reasons other than postprocedure care (i.e., social reasons) 58 . In other words, as a result of the VA’s unique same-day admission rate (observation status), the same-day admission triggers are not as effective.…”
Section: Discussionmentioning
confidence: 99%
“…We separately examined the following six diagnosis groups we believed to be likely at risk for switching from inpatient to outpatient following the example of past work, and based upon preliminary analyses and consultation with clinical colleagues: 102 (Non‐Specific Chest Pain), 245 (Syncope), 251 (Abdominal Pain), 133 (Other Lower Respiratory Disease), 159 (Urinary Tract Infections), and 55 (Fluid and Electrolyte Disorders) (Wright et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…It is likely that this increase has been at least partially driven by financial incentives from various payers including CMS; however, a more recent study by Wright and colleagues found similar increases in the Veterans Administration network which is internally funded and not subject to such incentives (Wright et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Access to health care Area deprivation index and area health resources [27,28] Age Age in years Comorbidities/multimorbidity Individual comorbidities and all combinations of 3 comorbidities; Charlson comorbidity index [29] Frailty Risk analysis index or claims-based frailty index [30,31] Health-related behaviors Receipt of applicable routine preventive care including annual wellness visits, indicated screening, and vaccinations; "Proportion of Days Covered" for chronic medications [23][24][25] Health-related knowledge Receipt of applicable routine preventive care including annual vaccinations [23][24][25] Male sex at birth Sex data Nursing home residence Active community living center admission or Medicare claims for skilled nursing care Occupation ZIP Code Median Income or Medicaid Eligibility Perceived risk of complications of COVID-19…”
Section: Dag Concept Proposed Operationalization Referencesmentioning
confidence: 99%